-x-2(x+1)=5(x-2)

Simple and best practice solution for -x-2(x+1)=5(x-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -x-2(x+1)=5(x-2) equation:


Simplifying
-1x + -2(x + 1) = 5(x + -2)

Reorder the terms:
-1x + -2(1 + x) = 5(x + -2)
-1x + (1 * -2 + x * -2) = 5(x + -2)
-1x + (-2 + -2x) = 5(x + -2)

Reorder the terms:
-2 + -1x + -2x = 5(x + -2)

Combine like terms: -1x + -2x = -3x
-2 + -3x = 5(x + -2)

Reorder the terms:
-2 + -3x = 5(-2 + x)
-2 + -3x = (-2 * 5 + x * 5)
-2 + -3x = (-10 + 5x)

Solving
-2 + -3x = -10 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
-2 + -3x + -5x = -10 + 5x + -5x

Combine like terms: -3x + -5x = -8x
-2 + -8x = -10 + 5x + -5x

Combine like terms: 5x + -5x = 0
-2 + -8x = -10 + 0
-2 + -8x = -10

Add '2' to each side of the equation.
-2 + 2 + -8x = -10 + 2

Combine like terms: -2 + 2 = 0
0 + -8x = -10 + 2
-8x = -10 + 2

Combine like terms: -10 + 2 = -8
-8x = -8

Divide each side by '-8'.
x = 1

Simplifying
x = 1

See similar equations:

| -2(3-4x)+5(2-1.6x)=4 | | 3x(x+2)-2=-(5+x)+x | | 5(4x+6)=3(2x+17) | | 4(2z-1)+3(4z-5)=z | | -2p+10+3p=55 | | 56=x-10 | | 435234x=2342 | | 3/5(d+5)=12 | | 257=5-4(1+8v) | | 4b+b=180 | | 8+3x-5=(x+3)-3(x+2)-1 | | 2(x-5)-(3x-1)=0 | | x-18=81 | | 4(2x-3)-4=3(2x-6) | | 5x+9=90-4 | | -46-5x=29 | | 2+4(x+2)=3x-2(x-5) | | 4x+7=6x-4x+29 | | 12-8w=-12 | | 3p-6p=12 | | 3(x-5)+10=2(x+4) | | 34-4x-3.14x=0 | | 6x-4+3x-1= | | (3x-1)+32=180 | | 12-4x-3.14x=0 | | 9r^2-18r+1=-4 | | 4(2x-3)-4=3x-4 | | 5x-2=15-42 | | 12-4x-pix=0 | | -5x+7-3x=-4x-5+2x | | 20=12+4k | | -3f/4=12 |

Equations solver categories